Patchy progress? Two decades of research on precariousness and precarious work in Australia. (2nd January 2018) - Campbell, Iain; Burgess, John
ABSTRACT: Precariousness, together with its cognate terms (e.g. precarity, precarious work, precarious workers, the precariat and precarious life), has become a significant theme in employment relations research in recent years. This paper reviews important aspects of the discussion, taking its starting point from an article in Labour and Industry which introduced the concept and sketched out a proposed research agenda for examining poor job quality in Australia. The current paper identifies patchy progress in knowledge concerning the core issues. Casual employment has been one area of successful inquiry, but challenges remain in connection with analysis of precariousness in permanent employment. At the same time, understanding of precariousness has moved into new channels of inquiry that were uncharted in the 1998 article and offer great promise for further research.